Coordinated Contribution of NADPH Oxidase- and Mitochondria-Derived Reactive Oxygen Species in Metabolic Syndrome and Its Implication in Renal Dysfunction - Lee, Hewang; Jose, Pedro A (Frontiers in Pharmacology, 2021)
Metabolic syndrome (MetS), a complex of interrelated risk factors for cardiovascular disease and diabetes, is comprised of central obesity (increased waist circumference), hyperglycemia, dyslipidemia (high triglyceride blood levels, low high-density lipoprotein blood levels), and increased blood pressure. Oxidative stress, caused by the imbalance between pro-oxidant and endogenous antioxidant systems, is the primary pathological basis of MetS. The major sources of reactive oxygen species (ROS) associated with MetS are nicotinamide-adenine dinucleotide phosphate (NADPH) oxidases and mitochondria. In this review, we summarize the current knowledge regarding the generation of ROS from NADPH oxidases and mitochondria, discuss the NADPH oxidase- and mitochondria-derived ROS signaling and pathophysiological effects, and the interplay between these two major sources of ROS, which leads to chronic inflammation, adipocyte proliferation, insulin resistance, and other metabolic abnormalities. The mechanisms linking MetS and chronic kidney disease are not well known. The role of NADPH oxidases and mitochondria in renal injury in the setting of MetS, particularly the influence of the pyruvate dehydrogenase complex in oxidative stress, inflammation, and subsequent renal injury, is highlighted. Understanding the molecular mechanism(s) underlying MetS may lead to novel therapeutic approaches by targeting the pyruvate dehydrogenase complex in MetS and prevent its sequelae of chronic cardiovascular and renal diseases.